Ketahanan Rumah Tangga Warga Binaan Pemasyarakatan (WBP) pada Lembaga Pemasyarakatan Perempuan Kelas III Mataram - Sumiati Sumiati; Rendra Khaldun (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Having a happy and harmonious home life is certainly everyone's dream. However, the course of married life is not always smooth and without obstacles. Married life is sometimes complicated and full of sharp stones or not always happy. So many have to stop in the middle of the road, but many are also able to make it to the end. This happened to the WBP Mataram Women's Prison where out of 203 prisoners there were 152 prisoners who were unable to maintain their married life. The reasons are different. For this reason, it is necessary to understand and know about the factors that influence divorce and the factors that influence household resilience, which can be used as a guide in carrying out domestic and marital life after serving a sentence. The concept of family resilience is very relevant because the concept of family resilience is in accordance with Islamic teachings and can be applied in efforts to realize family resilience. In order to be able to produce a generation of quality and of course useful for the nation and religion.